Effect of Mmolarity of HCl on production of Silica (SiO2) from Palm Oil Fuel Ash (POFA) - Durumin Iya, Sani Garba; Noh, Mohamad Zaky; AB RAZAK, Siti Noraiza; Alwi Kutty, Nur Azureen (Unique Research Publications, 2018)
Palm oil fuels ash (POFA) is a by-product from palm oil industries that constitutes of different compounds such as silica (SiO2), alumina (Al2O3) and many others, its abundances and improper disposal in waterways and as a landfill cause environmental pollution and hence need for its modification and usage. This paper presents an alternative way of producing silica from POFA. Untreated POFA was dried in an oven for 24 hours at a temperature of 110 °C and ground in a ball mill machine for 12 hours at a speed of 250 rev/s. After sieving, the powder was dispersed in 1 mole, 2 mole and 3 mole of HCl. An increase in the composition of SiO2 was observed using X-ray Fluorescence (XRF) analysis due to the increase in the molarity of acid, X-ray Diffraction analysis (XRD) and Scanning Electron Microscopy (SEM) shows that POFA has a crystalline and porous cellular structure. This shows that acidic wash treatment is good and an improved method for the production of silica from POFA